Today’s Criminal Environmental Enforcement Program: Why You May Be Vulnerable and Why You Should Guard Against Prosecution Through an Environmental Audit - Kris, Mary Ellen; Vannelli, Gail L. (Columbia Journal of Environmental Law, 2020)